PENGEMBANGAN PROSES COMPRESSION MOLDING DALAM PEMBUATAN EDIBLE FILM DARI TEPUNG KORO PEDANG (Canavalia ensiformis L.) [Development of Compression Molding Process for Edible Films Production from Canavalia ensiformis (L.) Flour] - Triana - Lindriati; Hari - Arbiantara (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Edible Films based on Canavalia Ensiformis flour could be made using compression molding process. This research was to investigate temperature (120oC, 130oC, 140oC) and pressure ( 0.845 Mpa, 1.690 Mpa, 2.540 Mpa) effect on the properties of the film. The compression-molding pressure significantly affected the film’s thickness, lightness, tensile strength, elongation and Water Vapor Transmition Rate (WVTR). Meanwhile molding temperature only affected film’s elongation (P<0.05) over the range of conditions studied. Increase in compaction pressure resulted in decreased thickness, tensile strength, elongation with increase in lightness (L*) and WVTR. Increasing the molding temperature decreased elongation. Flexible, light-yellow edible films could be produced at a processing temperature of 140oC and compaction pressure of 0.845 Mpa. The films thickness was 0.302 mm; lightness (L*) was 68.557, tensile strength was 4.091 Mpa, elongation was 37.547 % and WVTR was 0.001 mg/m2.det.